Registro e transferência de atletas de futebol: da contratação à resolução de conflitos - Nascimento, Matheus Laupman Lima Ferreira (2024)
This dissertation aims to demonstrate step by step how the registration and transfer of athletes in football works. After the Introduction, the research begins by describing the legal system through Lex Sportiva and its reception in the Brazilian legal system, in addition to the major milestones in the history of transfers and the registration of football athletes from 1848 to the present day. Then, part of the study is dedicated to the conceptualization of economic rights, the characterization of transfers and their subtypes, and the contracts and their peculiarities which govern this legal business. In the following chapter, the focus is on the details of FIFA's athlete registration regulations and the Brazilian Regulation issued by the Brazilian Football Confederation (CBF), called the National Football Athlete Transfer Registration Regulation (RNRTAF). The resolution of conflicts involving athlete registrations and transfers is the theme of the penultimate chapter of the work, highlighting how international and national arbitration have become an important tool for resolving disputes. Specific cases from FIFA bodies and the CBF National Dispute Resolution Chamber will be presented. To complete the dissertation, the figure of the athletes' agent is emphasized, a fundamental individual for football, often holding the direct power to intervene in the transfer and registration negotiations of these professionals